Bad Lung Down Phenomenon During Spinal Positioning for Hip Hemiarthroplasty: A Case Report - Putra, I Made Prema; Sudiantara, Putu Herdita; Aryawangsa, Anak Agung Ngurah; Wirananggala, Nyoman Bendhesa; Adistaya, Anak Agung Gde Agung; Senapathi, Tjokorda Gde Agung (JAI (Jurnal Anestesiologi Indonesia), 2021)
Background: Position-dependent hypoxemia during spinal anesthesia positioning is uncommon but may pose safety concerns in older patients with unilateral lung disease.Case: An 84-year-old woman (ASA III) with a proximal femoral fracture and clinical-radiographic features consistent with left-sided pneumonia was scheduled for bipolar hip hemiarthroplasty. Fracture-related pain and positioning limitations precluded the sitting position and right lateral decubitus, making the left lateral decubitus (LLD) position the only feasible option for spinal anesthesia. During LLD positioning with oxygen via nasal cannula, oxygen saturation dropped to 84-88% without dyspnea and promptly improved after returning to the supine position. Ancillary evaluation revealed preserved biventricular systolic function (left ventricular ejection fraction 60%, TAPSE 19 mm). Lung ultrasound showed no sonographic evidence of pulmonary edema. Spinal anesthesia was performed in the LLD position using 7.5 mg of 0.5% hyperbaric bupivacaine with 50 mcg intrathecal morphine. The surgery then proceeded with a supine-position modification, and hemodynamic and respiratory status remained stable without intraoperative complications.Discussion: In unilateral pneumonia, placing the diseased lung dependent can worsen ventilation-perfusion (V/Q) mismatch through the bad lung down phenomenon, leading to reversible position-dependent hypoxemia. In this case, desaturation occurred before intrathecal injection and before administration of sedatives or systemic opioids, making drug-induced hypoventilation unlikely. The absence of hypercapnic symptoms, preserved cardiac function, and lack of ultrasound evidence of pulmonary edema supported a predominantly pulmonary V/Q mechanism and illustrated silent hypoxemia in an older adult.Conclusion: Positioning should be regarded as a critical step in neuraxial anesthesia, particularly in frail or elderly patients with unilateral lung disease. In such patients, early detection of position-dependent desaturation and prompt correction of posture can allow surgery to proceed safely under regional anesthesia without the need to convert to general anesthesia.